Effect of Cooperative Teaching method on student Mathematics Achievement and Retention in Bayelsa State - Eze, Foluke Bosede (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study investigated the effect of the cooperative teaching method on student retention in elementary statistics in mathematics in Ogbia Local Government Area of Bayelsa State. Two research questions and two null hypotheses guided the study. The study employed the pretest posttest non equivalent control group design using two secondary schools randomly selected and classified into experimental and control groups. Two intact classes of eighty seven (87) Junior secondary school two (II) students from two secondary schools in Ogbia Local Government Area of Bayelsa State, Nigeria, were used. The instrument constructed by the researcher for the study is a Mathematics Achievement Test(MAT) validated by three mathematics educators. The reliability coefficient of 0.80 was obtained after the data collected from the test retest was analyzed using Cronbach alpha. Data collected from the instrument (MAT) was analyzed using mean and standard deviation to answer the research question and t-test statistics were used to test the hypotheses at alpha level ≤ 0.05. The findings revealed that the cooperative teaching method increased students' retention in mathematics and thus improved students' achievement. Hence, it was recommended that the cooperative teaching method be applied by teachers in mathematics teaching.